2020
DOI: 10.1029/2019gl085141
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Electron Acceleration Within Ion‐Scale Flux Rope

Abstract: Energetic electrons have frequently been observed in small‐scale flux ropes. However, whether these energetic electrons were energized directly within the flux rope or not is unknown. In this paper, we present concrete evidence provided by the Magnetospheric Multiscale mission that a secondary flux rope provided strong acceleration for electrons expelled by the reconnection X line. We find that the energetic electron fluxes inside the ion‐scale flux rope were larger than those outside the flux rope. Electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 70 publications
5
83
1
Order By: Relevance
“…In such a case, the long-term statistical characteristics of different electron PADs are very important dynamic properties of energetic electrons, which provide essential indicators to understand the physical processes of electron transport, energization, and loss (Liu et al, 2020;Ni, Zou, et al, 2016;Peng et al, 2020;Shi et al, 2016;Tang & Summers, 2019;H. Zhao et al, 2018;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, the long-term statistical characteristics of different electron PADs are very important dynamic properties of energetic electrons, which provide essential indicators to understand the physical processes of electron transport, energization, and loss (Liu et al, 2020;Ni, Zou, et al, 2016;Peng et al, 2020;Shi et al, 2016;Tang & Summers, 2019;H. Zhao et al, 2018;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There exists varied and partially overlapping terminology for such coherent structures: flux ropes (as twisted flux bundles), plasmoids (as plasma packets), and magnetic islands (as topologically isolated structures). Following Zhong et al (2020), this commentary will focus on flux ropes. Flux ropes break up extended current sheets, enhancing the rate at which plasma and magnetic flux may be transported throughout the system.…”
Section: Mesoscale Reconnection Structurementioning
confidence: 99%
“…This constellation of four spacecraft flies in a close‐packed tetrahedron that achieves fine spatial resolution via interspacecraft spacing of less than 10 km and correspondingly high temporal resolution for electromagnetic fields (FIELDS, Torbert et al, 2016), distribution functions (FPI, Pollock et al, 2016), and energetic particles (FEEPS, Blake et al, 2016). These capabilities were crucial for the study of Zhong et al (2020), where the most energetic particles were observed for only a few seconds.…”
Section: Flux Ropes In the Earth's Magnetotailmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that MFRs are important in the mass, magnetic flux, and energy transport in geospace, for instance, an MFR is the prototype of the flux transfer event at the magnetopause (Russell & Elphic, 1978). An MFR is also suggested as a site for significant particle energization (Chen et al, 2008; Huang et al, 2012; Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%